On the genetic diversity of Chimaera monstrosa Linnaeus, 1758 (Chordata, Chondrichthyes, Holocephali) in the Mediterranean Sea - Carugati, Laura; Cappelletti, Alice; Melis, Riccardo; Di Crescenzo, Simone; Bellodi, Andrea; Soler-Membrives, Anna; Follesa, Maria Cristina; Cannas, Rita (Frontiers in Fish Science, 2024)
The sustainable management and conservation of deep-sea species may be hampered by the paucity of data on their population structure and connectivity, in the face of ever-increasing fisheries pressure and other forms of impacts on deep-sea ecosystems. The rabbit fish, Chimaera monstrosa, is a deep-sea cartilaginous fish, reported worldwide in the past, but currently distributed only in the North-Eastern Atlantic Ocean and Mediterranean Sea. It is currently experiencing high levels of mortality associated with by-catch. Its slow growth, low fecundity and late maturity make this species particularly vulnerable to anthropogenic impact, although little is known about processes of connectivity between ecoregions. This study utilized DNA sequencing of the mitochondrial cytochrome c oxidase subunit I (COI) gene to investigate the population structure and demography of C. monstrosa both at the small (around the coasts of Sardinia, western Mediterranean Sea) and at larger spatial scales (at the pan-Mediterranean level, and between the Atlantic Ocean and the Mediterranean Sea). A total of 100 new sequences were obtained from specimens of Mediterranean origin, identifying 15 new haplotypes out of the 30 known so far for the species. Evidence of feeble but significant differentiation was detected among locations within the Tyrrhenian basin. Bayesian clustering analyses indicated the occurrence of three distinct haplogroups: the most common spread all over the Mediterranean, and the other two limited to the Western basin. Greater levels of genetic differentiation were found between the Atlantic and Mediterranean populations which constituted two main genetic clusters, with no shared haplotypes. The two populations became separated at the end of the Middle Pleistocene, with a clear sign of demographic expansion during the same period. The rabbit fish constitutes an important exception to a general paradigm of deep-sea species being connected by high levels of gene flow and such results could be useful to implement current management strategies to conserve this vulnerable by-caught species.